Fatores interferentes na análise eletrônica da qualidade do leite cru conservado com azidiol líquido, azidiol comprimido e bronopol. - Monica de Oliveira Leite (2006)
The objective of the present work was to evaluate the influence of several parameters on the results of electronic analyses of total bacteria count (TBC), the somatic cell count (SCC) and composition used to determine raw milk quality. The parameters were: storage time and temperature, azidiol (liquid and tablets) and bronopol. Each other analysis of SCC, composition and TBC. Six samples were collected, subdivided, added preservative and stored at room temperature for up to until eight days and incubated under three different temperatures (4, 7 e 10ºC) for until ten days. An electronic equipment, Bentley Combi System 2300® was used for the composition and SCC analyses. The total bacterial counting (TBC) was done using an electronic equipment Bactocount IBC - Bentley® and standard plate counting for mesophilic aerobic microorganisms. The design was split-splot, and the results were evaluated by Analysis of Variance with analysis of minimal significant difference by Duncan Test. The results showed that samples kept at 30ºC can be analyzed, for composition and SCC until the fourth and fifth day, respectively, after collection. Cooled samples can be analyzed for composition, SCC and TBC until 10 days after collection. However the samples can not be stored at room temperature for TBC. There was significant statistical difference on the levels of lactose and SCC between samples using azidiol. Therefore azidiol is not suitable for samples preservation analyzed for composition and SCC. Sample preserved with bronopol is not indicated for TBC because it underestimates the bacterial population. The results indicated that the tablet of azidiol can be used to replace the liquid presentation of the preservative in raw milk samples.